2021
DOI: 10.7153/fdc-2021-11-14
|View full text |Cite
|
Sign up to set email alerts
|

On the backward problems in time for time-fractional subdiffusion equations

Abstract: The backward problem for subdiffusion equation with the fractional Riemann-Liouville time-derivative of order ρ ∈ (0,1) and an arbitrary positive self-adjoint operator A is considered. This problem is ill-posed in the sense of Hadamard due to the lack of stability of the solution. Nevertheless, we will show that if we consider sufficiently smooth current information, then the solution exists and it is unique. Using this result, we study the inverse problem of initial value identification for subdiffusion equat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The uniqueness of the solution can be proved by the standard technique based on completeness of the set of eigenfunctions {v k } in H (see, e.g., [5]).…”
Section: Furthermore From Equation (2) One Hasmentioning
confidence: 99%
See 3 more Smart Citations
“…The uniqueness of the solution can be proved by the standard technique based on completeness of the set of eigenfunctions {v k } in H (see, e.g., [5]).…”
Section: Furthermore From Equation (2) One Hasmentioning
confidence: 99%
“…The backward problems in case (2) were studied in detail, for example, in [2][3][4]. The work [5] is devoted to the study of the backward problem in case (3). Therefore, in what follows we only consider the case α = 0.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Note that in work [18] the baclward problem for the subdiffusion equation ∂ α t u + Au = f was studied. It is shown that an estimate similar to (5.3) is valid only with the norm ||ω(T )|| 2 .…”
Section: Backward Problemmentioning
confidence: 99%